Models for the optimization of radio signaling capabilities in 5G systems - Pasarelski, Rosen (Yearbook Telecommunications, 2024)
Optimizing radio signaling capabilities in 5G systems involves various modeling techniques that can be systematized as follows - channel modeling, signal processing, optimization algorithms, queuing theory, machine learning, information theory, radio resource management, interference management, network topology and routing. The purpose of writing the article is to analyze mathematically the methods for optimizing radio signaling capabilities in 5G systems and to propose different models representing the behavior of the radio channel in variable environments and conditions. To consider algorithms and mathematical models for processing and analysis of radio signals received by gNB and user devices. To discuss mathematical models for analyzing and optimizing radio system performance in terms of delay, packet loss and throughput. Research and analysis of radio signaling capabilities in 5G systems, presentation of models related to the behavior of the radio channel in different environments and conditions, analysis of algorithms and mathematical models for processing and analysis of radio signals received from 5G base stations and end user devices can be noted as contributions to the development of the article.